The Role of Tarekat in Awakening the Spirit of Nationalism: Study of the Thought and Movement of Habib Luthfi bin Yahya - Gea Novita Rahma (Journal of Sufism and Psychotherapy, 2021)
The Sufism movement that transformed into a tarekat was a response to social and political conditions as well as nationalism. Habib Luthfi bin Yahya is one of the tarekat figures who focus on the issue of nationalism. The problem studied in the research is how Habib Luthfi bin Yahya thinks about the tarekat and nationalism and what movements are carried out in awakening the spirit of nationalism through the tarekat. This study uses a qualitative method through a sociological approach. Data collection techniques are by observation, interviews and documentation. Analysis of the data used is descriptive analytic that is exploring and clarifying about a phenomenon or social reality, by describing a number of variables with the problem and unit being studied, then analyzed in depth. The results of this study reveal that the tarekat according to Habib Lutfi bin Yahya is the path to Allah SWT, the tarekat is the fruit of the shari'ah. The source of the tarekat itself is the Qur'an and Hadith. The tarekat strengthens the position of nationalism, the tarekat experts feel they have the homeland given by Allah SWT as a form of gratitude for the grace of Allah SWT. Habib Luthfi bin Yahya said love for the homeland must be inflamed to avoid and threaten the nation’s disintegration. Habib Luthfi bin Yahya’s movement in awakening the spirit of nationalism is carried out through movements in various fields, including economic, cultural, political, religious, social, and environmental fields.